Prospective study of inflammatory response in patients submitted to abdominoplasty after bariatric surgery - Nádia de Rosso Giuliani; Miguel Modolin; Wilson Cintra; Rodrigo Itocazo Rocha; Rolf Gemperli (Revista Brasileira de Cirurgia Plástica)
Introduction: Obesity is a chronic inflammatory disease associated with changes in inflammatory markers such as interleukins and CRP. This study evaluates the inflammatory response, through variations in interleukins and CRP, in patients undergoing abdominoplasty. Methods: Fourteen patients underwent abdominoplasty after weight loss achieved through bariatric surgery to maintain weight loss for at least18 months. Il4, IL6, IL10 and PCR levels were verified at times: preoperative, during surgery, 24 hours after surgery, 7th postoperative day and 14th postoperative day. Results: IL4 increased in the 24 hours postoperatively and continued on the rise until the 14th day. IL10 went up during surgery and began to fall in the 24 hours postoperatively to levels lower than the initial ones. IL6 began to rise during surgery, being more expressive in the 24 hours postoperatively, followed by a fall until the 14th day. CRP increased 24 hours postoperatively and remained discharged until the 14th day. Conclusion: Abdominoplasty reduced the chronic inflammatory systemic condition.